2014
DOI: 10.1002/ijc.28854
|View full text |Cite
|
Sign up to set email alerts
|

Parental occupational pesticide exposure and the risk of childhood leukemia in the offspring: Findings from the childhood leukemia international consortium

Abstract: Maternal occupational pesticide exposure during pregnancy and/or paternal occupational pesticide exposure around conception have been suggested to increase risk of leukemia in the offspring. With a view to providing insight in this area we pooled individual level data from 13 case-control studies participating in the Childhood Leukemia International Consortium (CLIC). Occupational data were harmonized to a compatible format. Pooled individual analyses were undertaken using unconditional logistic regression. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 37 publications
(105 reference statements)
1
68
3
2
Order By: Relevance
“…13 For example, in a recent meta-analysis comprised 1,329 leukemia cases and 12,141 controls, Bailey et al described a doubled risk of childhood AML on maternal pesticides exposure during pregnancy. 29 Ferreira et al 11 also indicated 3.5 fold increased risk for AML in Brazilian children, on maternal exposure to organophosphate at different time points of pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…13 For example, in a recent meta-analysis comprised 1,329 leukemia cases and 12,141 controls, Bailey et al described a doubled risk of childhood AML on maternal pesticides exposure during pregnancy. 29 Ferreira et al 11 also indicated 3.5 fold increased risk for AML in Brazilian children, on maternal exposure to organophosphate at different time points of pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…Maternal occupational pesticide exposure during pregnancy and/or paternal occupational pesticide exposure around conception have indicated an increased risk of leukaemia in the offspring. Bailey et al (2014) pooled data from 13 case-control studies participating in the Childhood Leukaemia International Consortium (CLIC) and found a significant increased risk of acute myeloid leukaemia (AML) in children born from mothers exposed to pesticides during pregnancy (OR: 1.94; 95% CI: 1.19-3.18), which is consistent with previous meta-analyses; however, no significant risk was found for paternal exposure around conception (OR: 0.91; 95% CI: 0.66-1.24). In relation to acute lymphocytic leukaemia (ALL), Bailey et al (2014) observed a 20% increased risk with paternal exposure around conception (OR: 1.20; 95% CI: 1.06-1.38), which appeared to be more evident for children with T-cell ALL; however, no association was found between maternal exposure during pregnancy and risk of ALL (OR: 1.01; 95% CI: 0.78-1.30).…”
Section: Epidemiological Studies Linking Pesticide Exposure With Chilmentioning
confidence: 99%
“…19 Maternal occupational exposure to pesticides also increased the risk of childhood AML, whereas preconception paternal exposure slightly increased the risk of childhood ALL. 17 These findings are derived, for the most part, from other meta-analyses of published data. 32 -34 Childhood leukemia studies using dust samples and geographic information systems to assess indoor and outdoor pesticide exposure have S47 by guest on May 11, 2018 http://pediatrics.aappublications.org/ Downloaded from reported associations with specific types of pesticides based on target pest, phytochemical characteristics, or carcinogenicity.…”
Section: Pesticidesmentioning
confidence: 99%